la literatura de la "otra" Alemania - Fernández Bueno, Marta (Revista de Filología Alemana, 2010)
It was Professor Jaime Cerrolaza who presented me with what would be my first impressions of GDR literature. At that time, that country beyond the Iron Curtain still"really existed". The fall of the Berlin Wall and the end of the division of the world into two antagonistic blocs caused a social, political and individual collapse within the population in both East and West Germany, a change which necessarily led to a period of deep reflection. This contribution is intended as a double tribute: to the person who made it possible for me to know this reality, geographically and culturally so distant from our own, and to the memory of a vanished country, with its bright and dark sides. This paper is a response to the urgent need to delve into the past so as to be able to face the future. The playwright, novelist and essayist Christoph Hein will guide us through this complex reality, a reality which does not permit only one interpretation.